Analisis Penerapan Green Office di Lingkungan Kantor SMKS YPKP TIK SENTANI - Fikriyah Cahya Guniarti; Maria Natalia Paulus (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
This study aims to analyze the implementation of green office in the SMKS YPKP TIK Sentani office environment. Green Office refers to practices and policies that aim to reduce the environmental impact of office activities through energy efficiency, waste management, and the use of environmentally friendly materials. SMKS YPKP TIK Sentani is known to have received an award as an Adiwiyata school based on the decree of the Minister of Environment and Forestry of the Republic of Indonesia No. SK.1061/MENLK/P2SDM/SDM.2/10/2023. This research method uses a qualitative approach with in-depth interviews and observations to analyze the implementation of green office in the SMKS YPKP TIK Sentani office environment. The results of the study indicate that SMKS YPKP TIK Sentani employees have been active in implementing various green initiatives, such as waste sorting, reducing plastic use, saving electricity and water, planting plants, and the importance of awareness of the implementation of green office. Recommendations for further development include increasing training on environmentally friendly practices.